2018
DOI: 10.1016/j.neuroimage.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Domain-general and domain-specific neural changes underlying visual expertise

Abstract: Visual expertise induces changes in neural processing for many different domains of expertise. However, it is unclear how expertise effects for different domains of expertise are related. In the present fMRI study, we combine large-scale univariate and multi-voxel analyses to contrast the expertise-related neural changes associated with two different domains of expertise, bird expertise (ornithology) and mineral expertise (mineralogy). Results indicated distributed expertise-related neural changes, with effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 59 publications
2
29
0
5
Order By: Relevance
“…To examine the brain activity patterns underlying expert programmers' behavioral superiority, we employ a decoding framework that learns the relationship between multi-voxel activity patterns in the brain and functional categories of source code. This framework was motivated by prior studies that contrasted multi-voxel activity patterns of experts against novices and demonstrated that domain-specific expertise generally associates with representational changes in the brain [23][24][25][26] . Here we hypothesized that higher programming expertise relates to specific multi-voxel pattern representations, potentially influenced by their domain-specific knowledge and training experiences.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the brain activity patterns underlying expert programmers' behavioral superiority, we employ a decoding framework that learns the relationship between multi-voxel activity patterns in the brain and functional categories of source code. This framework was motivated by prior studies that contrasted multi-voxel activity patterns of experts against novices and demonstrated that domain-specific expertise generally associates with representational changes in the brain [23][24][25][26] . Here we hypothesized that higher programming expertise relates to specific multi-voxel pattern representations, potentially influenced by their domain-specific knowledge and training experiences.…”
Section: Introductionmentioning
confidence: 99%
“…While one should exercise caution in comparing the current findings, in which participants began their visual experience at a young age, with effects of visual experience in adults [58][59][60] , differences across studies highlight the possibility that developmental experience may be qualitatively different than that acquired in adulthood. First, childhood experience led to the development of a new representation to Pokémon that was anatomically consistent across participants and was coupled with increased responses and selectivity to 51,58,60 , it is unclear from our data whether these increased responses are due to experience or due to the fact that Pokémon have faces (Fig S9). Third, prior research has shown that learning contextual and semantic features of novel objects in adulthood (e.g., this object is found in gardens) can influence VTC representation 62 .…”
Section: Our Data Suggest That Individuals Who Have Undergone Life-lomentioning
confidence: 78%
“…A fogyasztói döntések előrejelzését célzó kutatások (Deppe, Schwindt, Kugel, Plassmann, & Kenning, 2005;Murawski, Harris, Bode, Dominguez, & Egan, 2012;Tusche, Bode, & Haynes, 2010;Van der Laan, Ridder, Viergever, & Smeets, 2012) a módszereken finomítva jellemzően az adott szituációban tanúsított fogyasztói viselkedést célozzák, mintsem a háttérben húzódó globális pszichológiai folyamatokat. Kutatásunkban feltételezzük, hogy az általunk alkalmazott ingerek mentális reprezentációi nem csupán egyetlen régióban, hanem különböző agyterületek komplex hálózatában tükröződnek (Kriegeskorte et al, 2006;Mitchell et al, 2008), így az objektumok felismeréséért felelős területeken túl magasabb szintű kognitív régiók is érintettek lehetnek (Mitchell et al, 2008;Tyler & Moss, 2001;Harel, Kravitz, & Baker, 2013;Martens, Bulthé, van Vliet, & Op de Beeck, 2018). Ráadásul az így nyert térképek teret nyitnak a márkaszemélyiség hátterében álló folyamatok megismerésének is.…”
Section: Irodalmi áTtekintésunclassified
“…arcok esetében mindannyiunk, de szakmától, tapasztalattól függően bizonyos ingerkategóriákra individuálisan) a domén-specifikus (pl. arcok feldolgozása), és a domén-általános (vizuális feldolgozás, vizuális azonosítás, vizuális figyelem) feldolgozási folyamatok eltérő alhálózatokat különböző mértékben aktiválnak (Martens et al, 2018;Harel et al, 2013;Bilalic, 2016). Kutatási modellünkben ismerősség és hungarikumság értékeket alkalmaztunk modulációként.…”
Section: Eredmények éS éRtékelésükunclassified
See 1 more Smart Citation